The PhoP/Q two-component regulatory system is essential for Xylella fastidiosa survival in Vitis vinifera grapevines. (January 2015) - Pierce, Brittany K.; Kirkpatrick, Bruce C.
Abstract: Xylella fastidiosa is a gram-negative, xylem-limited plant pathogenic bacterium that causes disease in a variety of economically important agricultural crops including Pierce's disease of grapevines. Quorum sensing is essential for X. fastidiosa to mediate pathogenicity in Vitis vinifera grapevines and subsequent transmission to other grapevines. Quorum sensing processes are regulated, to varying extent, by two-component regulatory systems. Here, we investigate the role of the PhoP/PhoQ two-component regulatory system, which is known to be involved in pathogenicity and survival of gram-negative bacterial pathogens of plants, humans and animals. Using insertional mutagenesis, we demonstrate that the PhoP/PhoQ two-component regulatory system is essential for X. fastidiosa survival in V. vinifera grapevines. Furthermore, we show PhoP/PhoQ is involved in regulation of density-dependent processes in vitro such as cell–cell aggregation and biofilm formation. We attempted to complement phoP and phoQ using the Pax1CM vector but were unsuccessful in generating a phoQ complement. The phoP complement we generated did not completely restore the wild-type phenotype although it did restore wild-type levels of phoP expression when the complement was grown on PD3 media. Our findings presented here demonstrate PhoP/PhoQ is responsible for regulating processes essential for X. fastidiosa survival in V. vinifera grapevines. Highlights: Function of the PhoP/Q two-component system in Xylella fastidiosa was investigated. PhoP/Q is essential for X. fastidiosa survival in planta . X. fastidiosa PhoP/Q is involved in regulation of density dependent processes. PhoP/Q mutants do not cause Pierce's disease of grapevine.